2009
DOI: 10.1007/s12562-009-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature characteristics in seed germination and growth of Zostera japonica Ascherson & Graebner from Ago Bay, Mie Prefecture, central Japan

Abstract: The optimal water temperature in seed germination and the upper critical water temperature in seedling growth were determined for Zostera japonica collected from Ago Bay, Japan. The relationship between the seed germination rates and seed storage period (0, 30, and 60 days) at 0°C was also examined. The optimal water temperature in seed germination was in the range 15-20°C regardless of the storage period, in which germination rates were up to 14%. Seedlings, grown from seeds up to 10 cm in total length, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In British Columbia, Z. japonica seedlings appear in March (Bigley, 1981;Harrison, 1982b). Freshly collected Z. japonica seeds from Japan exhibited low germination rates when placed in seawater at 10-23 • C without cold pre-treatment; subsequent exposure to fluctuating temperatures stimulated germination (Abe et al, 2009;Morita et al, 2011). However, a small proportion of the seeds may be non-dormant when shed and are capable of germinating in the absence of cold stratification, particularly under low salinity conditions (Morita et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In British Columbia, Z. japonica seedlings appear in March (Bigley, 1981;Harrison, 1982b). Freshly collected Z. japonica seeds from Japan exhibited low germination rates when placed in seawater at 10-23 • C without cold pre-treatment; subsequent exposure to fluctuating temperatures stimulated germination (Abe et al, 2009;Morita et al, 2011). However, a small proportion of the seeds may be non-dormant when shed and are capable of germinating in the absence of cold stratification, particularly under low salinity conditions (Morita et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, temperature and salinity cues may be important triggers for Z. japonica seed germination. Although Z. japonica seed germination in Japan is known to be strongly influenced by cold stratification (e.g., artificial cold exposure to mimic winter) and induction temperature (Abe et al, 2009;Morita et al, 2011), those experiments did not address salinity effects. Additionally, reviews highlighting factors known to influence seagrass seed germination call for further evaluation of the role of salinity in breaking dormancy (Orth et al, 2000(Orth et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Since there was no statistically significant difference by year, annual water temperature was not considered to be a factor for the decrease in shoot density, and annual water temperature was not a direct cause of the decrease in shoot density in both species after October 2011. Figure 8 shows the number of days in each year from 2010 to 2013 for which the daily mean water temperature was lower than 10°C; a temperature that may affect the germination of seagrass (Abe et al 2009;Kawasaki et al 1986). In 2011, the shoot density of Z. marina and Z. japonica was higher until June before the summer, and the number of days on which the daily mean water temperature was lower than 10°C was higher than in any other year at 43 days.…”
Section: Water Temperature and Solar Irradiationmentioning
confidence: 99%
“…The upper part of seagrass is affected by water turbulence, and the lower part is affected by photosynthesis inhibition (Dennison and Alberte 1985;Duarte 1991;Mach et al 2010;Kendrick et al 2002). The habitats of Z. marina and Z. japonica are affected by salinity and depth (Greve and Krausen-Jensen 2005;Morita et al 2010;Abe et al 2009;Shafer et al 2011). For example, in the summer, Z. marina growth becomes difficult when the daily mean water temperature is 28°C or more.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that Z. japonica has expanded its distributional area to the North Pacific Coast of North America [3,4]. There have been some ecological reports on the Z. japonica populations in the subtropical and temperate areas of Asia [5][6][7][8][9] and along the Pacific Coast of North America [3,[10][11][12][13][14][15][16][17][18][19]. However, there have been few physiological reports until now [19][20][21].…”
Section: Introductionmentioning
confidence: 99%